Impact-resistant PVC-U pipe and preparation method thereof
Through the synergistic toughening technology of nano calcium carbonate and modified powder nitrile rubber, the problem of easy destruction of PVC-U pipes under the action force is solved, the impact strength and heat resistance of the pipes are improved, and better comprehensive performance is achieved.
Patent Information
- Application Number
- CN202410481940.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-22
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-04-22
AI Technical Summary
Existing PVC-U pipes are prone to rapid cracking and damage when subjected to force, which affects their toughness. At the same time, toughening modification methods usually lead to a decrease in tensile strength and heat resistance.
The polyvinyl chloride resin is strengthened by synergistically strengthening the polyvinyl chloride resin by nano calcium carbonate and modified powder nitrile rubber. The modified powder nitrile rubber is prepared by radiation grafting technology, and amide groups and phenyl groups are introduced to improve compatibility and adhesion with polyvinyl chloride.
The impact strength, toughness, tensile strength and heat resistance of polyvinyl chloride pipes are improved, and the impact resistance is met.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of plastic pipes, in particular to an impact-resistant PVC-U pipe and a preparation method thereof. Background Art
[0002] Rigid polyvinyl chloride (PVC-U) pipe is one of the main pipe materials vigorously promoted by the country. It has the advantages of light weight, strong resistance to chemical corrosion, aging resistance, combustion support, not easy to clog, small resistance to conveying fluid, low price and easy installation. It is mainly used for building water supply and drainage, sewage discharge, wiring, ventilation, agricultural irrigation and other aspects.
[0003] However, polyvinyl chloride is a brittle material. When PVC-U pipes are made, large particles incompatible with PVC resin exist in the PVC pipes, such as decomposed PVC resin and agglomerated nano-calcium powder, which make the material of the PVC pipe uneven and introduce structural defects that cause stress concentration. As a result, the PVC-U pipes will crack and break quickly when subjected to force, affecting the toughness of the pipes.
[0004] At present, most of the methods for toughening and modifying PVC-U pipes are to achieve toughening and modification by blending elastomers with PVC. Although the toughness is enhanced after adding elastomers, the tensile strength and heat resistance of PVC-U pipes will decrease, which also limits the application of PVC-U pipes. Summary of the invention
[0005] In order to obtain a PVC-U pipe with good toughness, tensile strength and heat resistance, the present application provides an impact-resistant PVC-U pipe and a preparation method thereof.
[0006] The present application provides an impact-resistant PVC-U pipe and a preparation method thereof using the following technical solutions:
[0007] In a first aspect, the present application provides an impact-resistant PVC-U pipe, which is made of the following raw materials in parts by weight:
[0008] 100-110 parts of polyvinyl chloride resin;
[0009] 20-25 parts of nano calcium carbonate;
[0010] 6-10 parts of modified powdered nitrile rubber;
[0011] 2-5 parts of stabilizer;
[0012] Lubricant 0.5-1.5 parts;
[0013] 1-2 parts of stearic acid;
[0014] 1-3 parts of titanium dioxide;
[0015] 1-3 parts of brightener;
[0016] The modified powdered nitrile rubber is prepared by radiation grafting modified vinyl monomers into nitrile latex.
[0017] By adopting the above technical scheme, nano calcium carbonate is used as rigid particles, and modified powdered nitrile rubber is used as an elastomer. The polyvinyl chloride resin is toughened and strengthened by the synergistic effect of nano calcium carbonate / modified powdered nitrile rubber. The modified powdered nitrile rubber also promotes the dispersion of nano calcium carbonate in the polyvinyl chloride matrix, thereby increasing the impact strength and toughness of the polyvinyl chloride pipe, and enhancing the tensile strength and elastic modulus of the polyvinyl chloride pipe. By adding vinyl monomers to modify the powdered rubber, the bonding ability of the powdered rubber and polyvinyl chloride is improved, and the heat resistance of the polyvinyl chloride pipe is enhanced.
[0018] Optionally, the modified powdered nitrile rubber is prepared from the following raw materials in parts by weight:
[0019] 50-60 parts of nitrile latex;
[0020] Methacrylamide 15-20 parts;
[0021] 5-8 parts of divinylbenzene;
[0022] 3-6 parts of tetraethylenepentamine.
[0023] By adopting the above technical scheme, the powdered nitrile rubber is modified by methacrylamide and divinylbenzene, and amide groups and phenyl groups are introduced. By introducing monomers with similar chemical properties to polyvinyl chloride, the modified nitrile rubber has better compatibility with polyvinyl chloride, and by coating methacrylamide and divinylbenzene on the nitrile rubber particles, the elastic modulus and heat resistance are improved.
[0024] Optionally, the nitrile latex is selected from nitrile latex having a solid content of ≥30% and a cross-linking degree of ≥70%.
[0025] By adopting the above technical scheme, the semi-crosslinking of the nitrile rubber is controlled, which is beneficial to the bonding of the nitrile rubber and polyvinyl chloride and is beneficial to the performance of the toughening property of the nitrile rubber.
[0026] Optionally, the nano-calcium carbonate is selected from sodium salt of mono(2-ethylhexyl) phthalate modified nano-calcium carbonate, and the sodium salt of mono(2-ethylhexyl) phthalate modified nano-calcium carbonate is prepared from the following raw materials in parts by weight:
[0027] Phthalic anhydride 12-15 parts;
[0028] 10-12 parts of 2-ethylhexanol;
[0029] Sodium hydroxide 5-7 parts;
[0030] 90-95 parts of nano calcium carbonate.
[0031] By adopting the above technical scheme, sodium salt of mono(2-ethylhexyl) phthalate with phenyl is selected to modify nano-calcium carbonate, which can promote the dispersion synergy of modified nano-calcium carbonate and modified powdered nitrile rubber. The polar group at one end is chemically bonded to the nano-calcium carbonate, and the organic chain at the other end can improve the dispersibility of nano-calcium carbonate in the polyvinyl chloride matrix, which is beneficial to reduce the agglomeration of nano-calcium carbonate, and at the same time, the mechanical properties of the polyvinyl chloride pipe are improved.
[0032] Optionally, the stabilizer is any one or more of calcium stearate, zinc stearate, and methyl tin mercaptan.
[0033] Optionally, the lubricant is polyethylene wax.
[0034] Optionally, the particle size of the nano calcium carbonate is 30-50 nm.
[0035] By adopting the above technical solution and controlling the particle size, it is more conducive to the dispersion of nano calcium carbonate.
[0036] The present application also discloses a method for preparing an impact-resistant PVC-U pipe, comprising the following steps:
[0037] The polyvinyl chloride resin, nano calcium carbonate, modified powdered nitrile rubber, stabilizer, lubricant, stearic acid, titanium dioxide and brightener are mixed, heated and stirred to obtain a premix, the premix is put into a twin-screw extruder, extruded and cooled to room temperature to obtain an impact-resistant PVC-U pipe.
[0038] By adopting the above technical scheme, the toughening and reinforcing agent nano calcium carbonate, the modified powdered nitrile rubber, polyvinyl chloride and other additives are mixed and extruded together to obtain a PVC-U pipe with good toughness, tensile strength and heat resistance.
[0039] Optionally, the preparation method of the modified powdered nitrile rubber is as follows:
[0040] The nitrile latex is irradiated with 40-45 kGy under oxygen, the irradiated nitrile latex is placed in a three-necked flask, nitrogen is introduced for deoxygenation for 25-35 minutes, methacrylamide, divinylbenzene and tetraethylenepentamine are dissolved in a mixed solution of ethanol and water to obtain a modified solution, the modified solution is added to the three-necked flask, heated in a water bath at 55-60° C. with stirring, the product is vacuum dried at 50-60° C. after the reaction is completed, and extracted through a Soxhlet extractor to obtain a modified powdered nitrile rubber.
[0041] By adopting the above technical solution and preparing by pre-irradiation method, the grafting step is placed after irradiation, which is beneficial to improve the grafting rate and facilitate the separation from other homopolymers.
[0042] Optionally, when the nano calcium carbonate is modified by sodium salt of mono(2-ethylhexyl) phthalate, the preparation method is as follows:
[0043] Add phthalic anhydride to a reactor, stir and heat to 90-100° C., drop 2-ethylhexanol into the reactor, react at constant temperature for 1-1.5 hours, lower the temperature to 70-80° C., add a certain amount of sodium hydroxide aqueous solution, and react for 50-70 minutes to obtain sodium salt of mono(2-ethylhexyl)phthalate;
[0044] A certain amount of nano-calcium carbonate is subjected to ultrasonic treatment, and after the ultrasonic treatment, distilled water is added to prepare a nano-calcium carbonate suspension with a mass concentration of 10%-13%, the suspension is heated to 75-80° C., and sodium salt of mono(2-ethylhexyl) phthalate is added to the suspension under stirring conditions, and the reaction is carried out at a constant temperature for 1.5-2 hours;
[0045] After the reaction stops, the slurry is filtered, the filter cake is washed with anhydrous ethanol, and then dried and ground to obtain the sodium salt of mono(2-ethylhexyl) phthalate modified nano-calcium carbonate.
[0046] Optionally, the grafting of sodium salt of mono(2-ethylhexyl) phthalate onto the nano-calcium carbonate is achieved by wet modification.
[0047] In summary, this application has the following beneficial effects:
[0048] The powdered nitrile rubber is modified by methacrylamide and divinylbenzene, and amide and phenyl groups are introduced to improve the bonding ability between the powdered rubber and polyvinyl chloride. The polyvinyl chloride resin is toughened and strengthened by the synergistic effect of nano-calcium carbonate / modified powdered nitrile rubber. The modified powdered nitrile rubber also promotes the dispersion of nano-calcium carbonate in the polyvinyl chloride matrix, which can increase the impact strength and toughness of the polyvinyl chloride pipe, and enhance the tensile strength, elastic modulus and heat resistance of the polyvinyl chloride pipe. DETAILED DESCRIPTION
[0049] The present application is further described in detail below in conjunction with Examples 1-7 and Comparative Examples 1-2.
[0050] Preparation Example
[0051] Preparation Example 1
[0052] Preparation of modified powdered nitrile rubber
[0053] 50 kg of nitrile latex with a solid content of 44% and a crosslinking degree of 75% is irradiated for 40 kGy under oxygen, the irradiated nitrile latex is placed in a three-necked flask, and nitrogen is introduced for deoxygenation for 25 minutes, 15 kg of methacrylamide, 5 kg of divinylbenzene and 3 kg of tetraethylenepentamine are dissolved in a mixed solution of 30 kg of ethanol and 30 kg of water to obtain a modified liquid, the modified liquid is added to the three-necked flask, heated in a water bath at 55°C with stirring for 2 hours, and after the reaction is completed, the product is vacuum dried at 50°C and extracted through a Soxhlet extractor to obtain a modified powdered nitrile rubber.
[0054] Preparation Example 2
[0055] Preparation of modified powdered nitrile rubber
[0056] 60kg of nitrile latex with a solid content of 48% and a crosslinking degree of 80% is irradiated for 50kGy under oxygen, the irradiated nitrile latex is placed in a three-necked flask, and nitrogen is introduced for deoxygenation for 35 minutes, 20kg of methacrylamide, 8kg of divinylbenzene and 6kg of tetraethylenepentamine are dissolved in a mixed solution of 45kg of ethanol and 45kg of water to obtain a modified liquid, the modified liquid is added to the three-necked flask, heated in a water bath at 60°C with stirring for 2h, and after the reaction is completed, the product is vacuum dried at 60°C and extracted through a Soxhlet extractor to obtain a modified powdered nitrile rubber.
[0057] Preparation Example 3
[0058] Preparation of modified powdered nitrile rubber
[0059] 55 kg of nitrile latex with a solid content of 45% and a crosslinking degree of 78% was irradiated for 45 kGy under oxygen, the irradiated nitrile latex was placed in a three-necked flask, and nitrogen was introduced for deoxygenation for 30 minutes, 18 kg of methacrylamide, 6 kg of divinylbenzene and 5 kg of tetraethylenepentamine were dissolved in a mixed solution of 40 kg of ethanol and 40 kg of water to obtain a modified liquid, the modified liquid was added to the three-necked flask, heated in a water bath at 58° C. with stirring for 2 hours, and after the reaction, the product was vacuum dried at 55° C. and extracted through a Soxhlet extractor to obtain a modified powdered nitrile rubber.
[0060] Preparation Example 4
[0061] Preparation of a kind of nano calcium carbonate modified by sodium salt of mono(2-ethylhexyl) phthalate
[0062] 12 kg of phthalic anhydride was added to the reactor, heated to 90° C. with stirring, 10 kg of 2-ethylhexanol was added dropwise to the reactor, and the reaction was carried out at a constant temperature for 1 hour. The temperature was lowered to 70° C., 5 kg of sodium hydroxide was dissolved in 20 kg of water, and the sodium hydroxide aqueous solution was added to the reactor. After reacting for 50 minutes, sodium salt of mono(2-ethylhexyl)phthalate was obtained;
[0063] 90 kg of nano calcium carbonate with an average particle size of 30 nm was subjected to ultrasonic treatment, and distilled water was added after the ultrasonic treatment to prepare a nano calcium carbonate suspension with a mass concentration of 10%, and the suspension was heated to 75° C., and sodium salt of mono(2-ethylhexyl) phthalate was added to the suspension under stirring conditions, and the reaction was carried out at a constant temperature for 1.5 hours;
[0064] After the reaction stops, the slurry is filtered, the filter cake is washed with anhydrous ethanol, and then dried and ground to obtain the sodium salt of mono(2-ethylhexyl) phthalate modified nano-calcium carbonate.
[0065] Preparation Example 5
[0066] Preparation of a kind of nano calcium carbonate modified by sodium salt of mono(2-ethylhexyl) phthalate
[0067] 15 kg of phthalic anhydride was added to the reactor, heated to 100° C. with stirring, 12 kg of 2-ethylhexanol was added dropwise to the reactor, and the reaction was carried out at a constant temperature for 1.5 h. The temperature was lowered to 80° C., 7 kg of sodium hydroxide was dissolved in 28 kg of water, and the sodium hydroxide aqueous solution was added to the reactor. After reacting for 70 min, sodium salt of mono(2-ethylhexyl)phthalate was obtained;
[0068] 95 kg of nano calcium carbonate with an average particle size of 50 nm was subjected to ultrasonic treatment, and distilled water was added after the ultrasonic treatment to prepare a nano calcium carbonate suspension with a mass concentration of 13%, and the suspension was heated to 80° C., and sodium salt of mono(2-ethylhexyl) phthalate was added to the suspension under stirring conditions, and the reaction was carried out at a constant temperature for 2 hours;
[0069] After the reaction stops, the slurry is filtered, the filter cake is washed with anhydrous ethanol, and then dried and ground to obtain the sodium salt of mono(2-ethylhexyl) phthalate modified nano-calcium carbonate.
[0070] Preparation Example 6
[0071] Preparation of a kind of nano calcium carbonate modified by sodium salt of mono(2-ethylhexyl) phthalate
[0072] 14 kg of phthalic anhydride was added to the reactor, heated to 95° C. with stirring, 11 kg of 2-ethylhexanol was added dropwise to the reactor, and the reaction was carried out at a constant temperature for 1.5 h. The temperature was lowered to 75° C., 6 kg of sodium hydroxide was dissolved in 25 kg of water, and the sodium hydroxide aqueous solution was added to the reactor. After reacting for 60 min, sodium salt of mono(2-ethylhexyl)phthalate was obtained;
[0073] 92 kg of nano calcium carbonate with an average particle size of 40 nm was subjected to ultrasonic treatment, and distilled water was added after the ultrasonic treatment to prepare a nano calcium carbonate suspension with a mass concentration of 12%, and the suspension was heated to 80° C., and sodium salt of mono(2-ethylhexyl) phthalate was added to the suspension under stirring conditions, and the reaction was carried out at a constant temperature for 1.5 hours;
[0074] After the reaction stops, the slurry is filtered, the filter cake is washed with anhydrous ethanol, and then dried and ground to obtain the sodium salt of mono(2-ethylhexyl) phthalate modified nano-calcium carbonate.
[0075] Example
[0076] The brightener used in the following examples is ob-1, which is from Sichuan Xintianhai Chemical Co., Ltd.
[0077] The polyvinyl chloride resin is HS-74-3AE106, from Dongguan Dongying Plastic Co., Ltd.;
[0078] The polyethylene wax used is A-C316A, which comes from Guangdong Dingxin Polymer Technology Co., Ltd.
[0079] Example 1
[0080] Preparation of impact-resistant PVC-U pipe
[0081] 100 kg of polyvinyl chloride resin, 20 kg of nano calcium carbonate with an average particle size of 30 nm, 6 kg of modified powdered nitrile rubber, 2 kg of zinc stearate, 0.5 kg of polyethylene wax, 1 kg of stearic acid, 1 kg of titanium dioxide and 1 kg of brightener are put into a high-speed mixer for mixing, stirred at a speed of 1000 rpm and gradually heated to 60° C., stirred for 20 minutes to obtain a premix, put the premix into a twin-screw extruder for extrusion molding at a temperature of 170° C., cooled to room temperature, and obtained an impact-resistant PVC-U pipe.
[0082] The modified powdered nitrile rubber is prepared by radiation grafting methyl methacrylate onto nitrile latex, and the steps are as follows: diluting the nitrile latex with a solid content of 45% with 1% ammonia water, adding methyl methacrylate to the diluted latex, stirring and mixing evenly, and then 60 The irradiation is carried out in a radiation device at a dose of 40 kGy, β-cyclodextrin and fumed silica are added to the irradiated latex as a release agent, and the latex is dried by a spray drying method to obtain a modified powdered nitrile rubber.
[0083] Example 2
[0084] Preparation of impact-resistant PVC-U pipe
[0085] 100 kg of polyvinyl chloride resin, 20 kg of nano calcium carbonate with an average particle size of 30 nm, 6 kg of modified powdered nitrile rubber obtained in Preparation Example 1, 2 kg of zinc stearate, 0.5 kg of polyethylene wax, 1 kg of stearic acid, 1 kg of titanium dioxide and 1 kg of brightener are put into a high-speed mixer for mixing, stirred at a speed of 1000 rpm and gradually heated to 60° C., stirred for 20 minutes to obtain a premix, the premix is put into a twin-screw extruder for extrusion molding at 170° C., cooled to room temperature, and an impact-resistant PVC-U pipe is obtained.
[0086] Example 3-Example 7
[0087] The difference between Example 3 to Example 7 and Example 1 is that the amount and type of raw materials used in preparing the PVC-U pipe are different, as shown in Table 1.
[0088] Table 1
[0089]
[0090]
[0091] Comparative Example
[0092] Comparative Example 1
[0093] The difference between this comparative example and Example 1 is that in this comparative example, no modified powdered nitrile rubber is added to the raw material of the PVC-U pipe.
[0094] The preparation method of the PVC-U pipe is the same as that in Example 1.
[0095] Comparative Example 2
[0096] The difference between this comparative example and Example 1 is that in this comparative example, unmodified powdered nitrile rubber is added to the raw material of the PVC-U pipe.
[0097] The preparation method of the PVC-U pipe is the same as that in Example 1.
[0098] Performance Testing
[0099] Impact resistance: Tested according to GB / T 1843-2008 "Determination of Izod Impact Strength of Plastics". Before testing, the samples of Examples 1-7 and Comparative Examples 1-2 were placed at a temperature of 23°C and a relative humidity of 50% for 20 hours. Notch type: Type A. The results are recorded in Table 2.
[0100] Heat resistance: Test with reference to GB / T 8802-2001 "Determination of Vicat softening temperature of thermoplastic pipes and fittings" and record the results in Table 2.
[0101] Tensile strength: refer to GB / T 8804.2-2003 "Determination of tensile properties of thermoplastic pipes" for testing and record the results in Table 2.
[0102] Longitudinal shrinkage rate: refer to GB / T 6671-2001 "Determination of longitudinal shrinkage rate of thermoplastic plastic pipes" for testing and record the results in Table 2.
[0103] Table 2
[0104]
[0105]
[0106] Result analysis:
[0107] Example 1 of the present application selects methyl methacrylate as the radiation grafting monomer and adopts the co-irradiation grafting method for modification. The prepared PVC-U pipe meets the national standard requirements in terms of notched impact strength, Vicat softening temperature, tensile strength and longitudinal shrinkage rate, and meets the standards of Vicat softening temperature ≥79°C, tensile strength ≥40MPa, and longitudinal elongation rate ≤5%, and the notched impact strength is greatly improved, indicating that the toughness of the polyvinyl chloride pipe is enhanced, the comprehensive performance is improved, and the impact-resistant use requirements are met.
[0108] In Example 2-4, for the modified polyethylene monomer, methacrylamide and divinylbenzene were selected and mixed in a ratio of (15-20): (5-8), and the grafting modification was carried out by pre-irradiation method. Compared with Example 1, the impact resistance and heat resistance were further improved. This is because amide group and phenyl group were introduced into the modified powdered nitrile rubber, the molecular chain was further enlarged, and the compatibility with polyvinyl chloride was better. It was also more conducive to the dispersion of nano-calcium carbonate in the matrix and more conducive to the formation of a cross-linking system to exert toughening and strengthening effects.
[0109] In Example 5-7, sodium salt of mono(2-ethylhexyl) phthalate modified nano-calcium carbonate was selected from the raw materials of PVC-U, and polar sodium salt of mono(2-ethylhexyl) phthalate was coated on the surface of the nano-calcium carbonate to reduce the agglomeration of the nano-calcium carbonate, improve the dispersibility of the nano-calcium carbonate, and further enhance the mechanical properties of the polyvinyl chloride pipe.
[0110] In Comparative Example 1, no modified powdered nitrile rubber was added to the raw materials of the PVC-U pipe, and only nano-calcium carbonate was selected as the toughening material. In Comparative Example 2, unmodified powdered nitrile rubber was added. Compared with Example 1, the impact strength of Comparative Example 1-2 decreased significantly, highlighting the synergistic toughening effect of modified powdered nitrile rubber / nano-calcium carbonate on the polyvinyl chloride pipe.
[0111] The embodiments of this specific implementation are all preferred embodiments of this application, and are not intended to limit the protection scope of this application. Therefore, any equivalent changes made based on the structure, shape, and principle of this application should be included in the protection scope of this application.
Claims
1. An impact-resistant PVC-U pipe, characterized in that: Made from the following raw materials in parts by weight: 100-110 parts of polyvinyl chloride resin; 20-25 parts of nano calcium carbonate; 6-10 parts of modified powdered nitrile rubber; 2-5 parts of stabilizer; Lubricant 0.5-1.5 parts; 1-2 parts of stearic acid; 1-3 parts of titanium dioxide; 1-3 parts of brightener; The modified powdered nitrile rubber is prepared by radiation grafting methacrylamide and divinylbenzene into nitrile latex; the nano calcium carbonate is modified by sodium salt of mono(2-ethylhexyl) phthalate.
2. The impact-resistant PVC-U pipe according to claim 1, characterized in that: The modified powdered nitrile rubber is prepared from the following raw materials in parts by weight: 50-60 parts of nitrile latex; Methacrylamide 15-20 parts; 5-8 parts of divinylbenzene; 3-6 parts of tetraethylenepentamine.
3. The impact-resistant PVC-U pipe according to claim 2, characterized in that: The nitrile latex is selected from nitrile latex with a solid content of ≥30% and a cross-linking degree of ≥70%.
4. The impact-resistant PVC-U pipe according to claim 1, characterized in that: The sodium salt of mono(2-ethylhexyl)phthalate modified nano calcium carbonate is prepared from the following raw materials in parts by weight: Phthalic anhydride 12-15 parts; 10-12 parts of 2-ethylhexanol; Sodium hydroxide 5-7 parts; 90-95 parts of nano calcium carbonate.
5. The impact-resistant PVC-U pipe according to claim 1, characterized in that: The stabilizer is selected from any one or more of calcium stearate, zinc stearate, and methyl tin mercaptan.
6. The impact-resistant PVC-U pipe according to claim 1, characterized in that: The lubricant is polyethylene wax.
7. The impact-resistant PVC-U pipe according to claim 1, characterized in that: The particle size of the nano calcium carbonate is 30-50nm.
8. The method for preparing an impact-resistant PVC-U pipe according to any one of claims 1 to 7, characterized in that: The steps include: The polyvinyl chloride resin, nano calcium carbonate, modified powdered nitrile rubber, stabilizer, lubricant, stearic acid, titanium dioxide and brightener are mixed, heated and stirred to obtain a premix, the premix is put into a twin-screw extruder, extruded and cooled to room temperature to obtain an impact-resistant PVC-U pipe.
9. The method for preparing an impact-resistant PVC-U pipe according to claim 8, characterized in that: The preparation method of the modified powdered nitrile rubber is as follows: The nitrile latex is irradiated with 40-45 kGy under oxygen, the irradiated nitrile latex is placed in a three-necked flask, nitrogen is introduced for deoxygenation for 25-35 minutes, methacrylamide, divinylbenzene and tetraethylenepentamine are dissolved in a mixed solution of ethanol and water to obtain a modified solution, the modified solution is added to the three-necked flask, heated in a water bath at 55-60° C. with stirring, the product is vacuum dried at 50-60° C. after the reaction is completed, and extracted through a Soxhlet extractor to obtain a modified powdered nitrile rubber.
10. The method for preparing an impact-resistant PVC-U pipe according to claim 8, characterized in that: When the nano calcium carbonate is modified by sodium salt of mono(2-ethylhexyl) phthalate, the preparation method is as follows: Add phthalic anhydride to a reactor, stir and heat to 90-100° C., drop 2-ethylhexanol into the reactor, react at constant temperature for 1-1.5 hours, lower the temperature to 70-80° C., add a certain amount of sodium hydroxide aqueous solution, and react for 50-70 minutes to obtain sodium salt of mono(2-ethylhexyl)phthalate; A certain amount of nano-calcium carbonate is subjected to ultrasonic treatment, and after the ultrasonic treatment, distilled water is added to prepare a nano-calcium carbonate suspension with a mass concentration of 10%-13%, the suspension is heated to 75-80°C, and sodium salt of mono(2-ethylhexyl) phthalate is added to the suspension under stirring conditions, and the reaction is carried out at a constant temperature for 1.5-2h; After the reaction stops, the slurry is filtered, the filter cake is washed with anhydrous ethanol, and then dried and ground to obtain the sodium salt of mono(2-ethylhexyl) phthalate modified nano-calcium carbonate.
Citation Information
Patent Citations
Special material for PVC pipe and preparation method thereof
CN102504434A
Valeronitrile latex and preparation method thereof
CN113024735A